Cigarette smoking and the risk of nasopharyngeal carcinoma: a meta-analysis of epidemiological studies. Issue 10 (5th October 2017) - Long, Mengjuan; Fu, Zhenming; Li, Ping; Nie, Zhihua
Abstract : Objective: The role of cigarette smoking as an independent risk factor for patients with nasopharyngeal carcinoma (NPC) is controversial. We attempted to provide evidence of a reliable association between cigarette smoking and the risk of NPC. Design: Meta-analysis. Data sources: PubMed online and the Cochrane Library of relevant studies published up to February 2016. Eligibility criteria: All studies had to evaluate the relationship between NPC and cigarette smoking with never smokers as the reference group. Outcomes: The primary outcome was the adjusted OR, RR or HR of NPC patients comparing smoking with never-smoking; the second was the crude OR, RR or HR. Results: We identified 17 case–control studies and 4 cohort studies including 5960 NPC cases and 429 464 subjects. Compared with never smokers, current smokers and ever smokers had a 59% and a 56% greater risk of NPC, respectively. A dose–response relationship was identified in that the risk estimate rose by 15% (p<0.001) with every additional 10 pack-years of smoking, and risk increased with intensity of cigarette smoking (>30 cigarettes per day). Significantly increased risk was only found among male smokers (OR, 1.36; 95% CI 1.15 to 1.60), not among female smokers (OR, 1.58; 95% CI 0.99 to 2.53). Significantly increased risk also existed in the differentiated (OR, 2.34; 95% CI 1.77 to 3.09) and the undifferentiated type of NPC (OR, 1.15; 95% CI 0.90 to 1.46). Moreover, people who started smoking at younger age (<18 years) had a greater risk than those starting later for developing NPC (OR, 1.78; 95% CI 1.41 to 2.25). Conclusions: Cigarette smoking was associated with increased risk of NPC, especially for young smokers. However, we did not find statistical significant risks of NPC in women and in undifferentiated type, which might warrant further researches.